Should exercises be painful in the management of chronic musculoskeletal pain?: a systematic review and meta-analysis - Smith, Benjamin E.; Hendrick, Paul; Smith, Toby O.; Bateman, Marcus; Moffatt, Fiona; Rathleff, Michael Skovdal; Selfe, James; Logan, Pip (BMJ Publishing Group, 2017)
Background: Chronic musculoskeletal disorders are a prevalent and costly global health issue. A new form of exercise therapy focused on loading and resistance programmes that temporarily aggravates a patient’s pain has been proposed. The object of this review was to compare the effect of exercises where pain is allowed/encouraged, compared with non-painful exercises on pain, function or disability in patients with chronic musculoskeletal pain within randomised controlled trials.